Effect Of Non-Ballistic Active Knee Extension In Neural Slump Position On Hamstring Flexibility - Nishant Kumar Bali; Deepak Raghav; Tanvi Agrawal; Prabhu Ram Krishnapandian (Journal of Advanced Zoology, 2024)
PURPOSE :- To assess how neural slump mobilization affects hamstring flexibility BACKGROUND :- Thirty adult individuals in good health with restricted right hamstring flexibility (minimum of 15 degrees less active knee extension assessed with femur held at 90 degrees of hip flexion) were divided into two groups at random. METHOD:- Subjects in Group A will engage in non-ballistic static stretching for 30 seconds, which will be followed by static stretching for 30 seconds after a 5-minute rest period for two weeks. Group-B: Over the course of two weeks, the subject will complete static stretches maintained for 30 seconds, repeated five times, with a 1-second break in between each stretch. STATICAL ANALYSIS :- To compare the mean value for pre-treatment and post-treatment ROM across groups as well as the comparison of the mean values for pre-treatment and post-treatment ROM within the group, independent sample t-test and paired t-test were employed, respectively. A value of p was chosen.05 RESULT:- According to a within-group analysis, group A’s mean range of motion was larger after therapy than it was before treatment (53.83 2.43), and this difference was determined to be statistically significant (p=0.00). The difference between the mean post-treatment range of motion value for group B (51.44 2.63) and the mean pre-treatment range of motion value (38.49 3.26) was determined to be statistically significant (p=0.00). The results of the between-group analysis showed that group A’s mean post-treatment range of motion value was greater than group B’s (53.83 2.43 vs. 51.44 2.63), and this difference was judged to be statistically significant (p=0.016). CONCLUSION :- The results of the current study showed that static stretching combined with the neural slump posture improved hamstring flexibility in adults more than static stretching alone, resulting in changes in the accuracy of the active knee extension measurement